The Effect of Environmental, Social, and Governance (ESG) Performance on the Financial Outcomes of Manufacturing Firms Listed on the Indonesia Stock Exchange. - Semuel Pajala (Institute of Advanced Knowledge and Science, 2026)
Financial performance in manufacturing firms is no longer determined solely by economic and operational factors but is also influenced by the implementation of sustainable business practices through Environmental, Social, and Governance (ESG) initiatives. Although ESG adoption has grown significantly in Indonesia, empirical evidence regarding its impact on the financial performance of manufacturing firms remains inconclusive. Therefore, this study aims to examine the effect of ESG performance on the financial performance of manufacturing firms listed on the Indonesia Stock Exchange. This study employs a quantitative research approach using secondary panel data obtained from the annual reports and sustainability reports of manufacturing firms listed on the Indonesia Stock Exchange during the 2020–2024 period. ESG performance is used as the independent variable, while financial performance is measured using Return on Assets (ROA), Return on Equity (ROE), and Tobin's Q. Panel data regression analysis is applied to test the relationship between ESG performance and corporate financial performance. The results reveal that ESG performance has a positive and statistically significant effect on corporate financial performance. Firms with higher ESG performance tend to achieve greater profitability and higher market valuation. These findings indicate that the adoption of sustainable business practices enhances operational efficiency, strengthens stakeholder trust, and creates long-term corporate value. In conclusion, ESG implementation represents a strategic factor in improving the financial performance of manufacturing firms. Accordingly, companies should integrate ESG principles into their business strategies to enhance sustainable competitiveness while creating value for investors, stakeholders, and sustainable industrial development.